2012
DOI: 10.1007/s00221-012-3187-4
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric inhibition in human wrist muscles

Abstract: The interhemispheric interactions between homologous wrist extensor and flexor muscles representations in the right and left primary cortex (M1) were studied using a paired-pulse transcranial magnetic stimulation in healthy subjects. The magnitude of interhemispheric inhibition (IHI) was studied in 9 right-handed subjects at short (10 ms, SIHI) and long (40 ms, LIHI) interstimulus intervals between the magnetic conditioning (CS) and test stimulus in the motor dominant to non-dominant cortex and vice versa, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…In normal subjects we had previously shown that SIHI was more bidirectionally reduced than LIHI in wrist muscles in comparison with rest during a postural task (holding a pen as in the present study) involving the hand contralateral to the CS stimulation. This was more pronounced for the ECR than for the FCR muscle . These results fit those of Nelson et al, who described a bidirectional decrease of IHI for flexor digitorum indicis (FDI) muscles when the subjects performed isometric contraction of the FDI muscle in the context of holding a pen.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In normal subjects we had previously shown that SIHI was more bidirectionally reduced than LIHI in wrist muscles in comparison with rest during a postural task (holding a pen as in the present study) involving the hand contralateral to the CS stimulation. This was more pronounced for the ECR than for the FCR muscle . These results fit those of Nelson et al, who described a bidirectional decrease of IHI for flexor digitorum indicis (FDI) muscles when the subjects performed isometric contraction of the FDI muscle in the context of holding a pen.…”
Section: Discussionsupporting
confidence: 90%
“…A possible explanation is the predominant involvement of flexor muscles in the dystonic hand of most of our patients and also a possible decrease in reciprocal inhibition . The physiologically weaker FCR contraction compared with ECR contraction observed in normal subjects when holding a pen may have also amplified these differences . However, although IHI disturbances were observed bilaterally in both muscles and only in patients with mirror dystonia, background FCR EMG differences were strictly unilateral and observed in both patient groups, and so their impact was likely minor.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Alternatively, if CR operates in a more specific manner, then we expected to observe greater inhibition in the condition involving homologous response alternatives. Competitive interhemispheric interactions reflecting the mirror organization of the motor system have been observed in many behavioral and physiological studies (Diedrichsen, Wiestler, & Krakauer, 2013; Sattler, Dickler, Michaud, & Simonetta-Moreau, 2012; Hinder, Schmidt, Garry, & Summers, 2010). As such, competition is likely to be related to the degree of similarity between the response alternatives.…”
Section: Introductionmentioning
confidence: 97%